The potential of type species to destabilise the taxonomy of zooxanthellate Scleractinia - Veron, J.e.n. (Zootaxa, 2015)
The ongoing demise of zooxanthellate Scleractinia from world-wide environmental deterioration has prompted a very large number of people including aquarists, managers, students, conservationists and scientists to work on reef corals. These people have a right to expect their various endeavors to be based on a nomenclature derived from taxonomic studies rather than human-created rules. Clearly there must be an amalgamation of the two; however a decade-long construction of a website on zooxanthellate Scleractinia has revealed that 15% of all genera, most with a history extending back to the 18th century and involving over 100 species, are vulnerable to name changes that are readily avoidable.